Mixed vegetable juices acidified with sauerkraut juice and preserved using high pressure or heat pasteurisation treatments nutritional and sensory evaluation - Gabrovska, D., Food Research Institute, Prague (Czech Republic); Ouhrabkova, J., Food Research Institute, Prague (Czech Republic); Rysova, J., Food Research Institute, Prague (Czech Republic); Holasova, M., Food Research Institute, Prague (Czech Republic); Fiedlerova, V., Food Research Institute, Prague (Czech Republic); Laknerova, I., Food Research Institute, Prague (Czech Republic); Winterova, R., Food Research Institute, Prague (Czech Republic); Eichlerova, E., Food Research Institute, Prague (Czech Republic); Erban, V., Food Research Institute, Prague (Czech Republic); Strohalm, J., Food Research Institute, Prague (Czech Republic); Nemeckova, I., Dairy Research Institute, Prague (Czech Republic); Houska, M., Food Research Institute, Prague (Czech Republic) (Czech Journal of Food Sciences, 2014)
The goal of this work was to design mixed vegetable (vegetable-fruit) juices which are preserved by high pressure, have an increased content of bioactive substances, are made from locally available produce, and offer excellent nutrition and appealing taste. The new products were prepared on laboratory scale units and underwent nutritional, microbiological, and sensory evaluations. The basic composition, total polyphenol content, ascorbic acid content, and total antioxidant activity were determined.